Real Wages and the Business Cycle in Germany - Thomas Beissinger; Martyna Marczak (Verein für Socialpolitik, 2010)
This paper analyzes the cyclicality of real consumer wages and real producer wages in Germany. In order to scrutinize whether the empirical results are robust to the detrending method, we apply the deterministic trend model, the Beveridge-Nelson decomposition, the Hodrick-Prescott filter, the Baxter-King filter and the structural time series model to both real wage series and GDP. The detrended data are analyzed, both in the time domain and in the frequency domain. The great advantage of an analysis in the frequency domain is that it allows to assess the relative importance of particular frequencies for the behavior of real wages.
Keywords: E32; C32; J30; 330; Real wages; business cycle; frequency domain; time domain; trend-cycle estimation; structural time series model; Germany